ANALYSIS OF THE STRATEGIC ENVIRONMENT IN THE DEVELOPMENT OF BUSINESS SERVICES BULUKUMBA - Suhaeni Suhaeni; Nurman, Chalid Imran Musa, Hety Budiyanti, Muhammad Ilham Wardhana Haerudin (BORJUIS: JURNAL OF ECONOMY, 2024)
This study aims: (1) to describe the management of the Kurirta Bulukumba service enterprise, (2) to analyze the internal and external environment of Kurirta bulukumba services company, (3) to define the formulation of the business development strategy used in Kurirta Bullukumba Service Company, and (4) to described the results of the analysis Strenghts, Weaknesses, Opportunities and Threats in Kurerta Bulukumbas service company. This type of research is qualitative research with a descriptive approach. The total sample in this study was 15 people from Kurirta Bulukumba's employees and partners. Data collection is done using observations, interviews, lifts and documentation. The data analysis was carried out using the SWOT Analysis method with the help of Internal Strategic Factor Analysis Summary (IFAS) and External Strategic Faktor Analysis summary (EFAS). The results from IFAS, EFAS were 1.96 and 1.16 which indicated that the company was in the quarter I position (positive, positive) where the company is in a strong position and opportunity. So it can be formulated the strategy used for the company is an aggressive strategy or growth strategy that is the expansion of new territory using the extensive network and the experience of the area that Kurirta Bulukumba has.